Coating and preparation method thereof, neodymium-iron-boron base material with coating and neodymium-iron-boron magnet

By using characteristically modified PVB resin and alloy powder coating, the problems of coating fluidity and thixotropy after coating light rare earth elements are solved, and the uniformity of the coating layer and the magnetic performance of the neodymium iron boron magnet are improved.

CN119307136APending Publication Date: 2025-01-14BEIJING ZHONG KE SAN HUAN HI TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310855343.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-12
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

After coating light rare earth elements instead of heavy rare earth elements, the coating has poor fluidity, unstable thixotropy and high temperature sensitivity, resulting in poor uniformity of the coating layer thickness, affecting the magnetic properties of the magnets to fluctuate greatly, especially small The HcJ magnetic properties of the product are greatly affected.

Method used

Using coatings including PVB resin and alloy powder, the molecular chain ends of the PVB resin have amino and/or amide groups, the main chain side groups include butyral groups, hydroxyl groups and acetoxy groups, and the alloy powder component is (HRe(1-x)LRex )aT100-a-bMb, through specific addition sequences and process conditions, a coating with good fluidity, low thixotropy and low temperature sensitivity is prepared.

Benefits of technology

It improves the plasticity and coating uniformity of the coating, reduces the fluctuations in the weight gain of the coating, and significantly improves the magnetic properties of neodymium iron boron magnets, especially the stability of HcJ magnetic properties of small products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307136A_ABST
    Figure CN119307136A_ABST
Patent Text Reader

Abstract

The invention provides a coating and a preparation method thereof, a neodymium-iron-boron base material with a coating and a neodymium-iron-boron magnet. The coating comprises PVB (Polyvinyl Butyral) resin and alloy powder, wherein the tail end of a molecular chain of the PVB resin comprises an amino group and / or an amido group, and side groups of a main chain of the molecular chain of the PVB resin comprise a butyral group, a hydroxyl group and an acetoxyl group; the alloy powder has the following composition: (HRe (1-x) LRex) aT100-a-bMb. Wherein HRe comprises Tb and / or Dy; lRe comprises one or more than two of Nd, Pr, La and Ce; t comprises Fe and / or Co; m comprises one or more than two of Al, Ga, Cu, Zn, Sn, Ni and Si; 0.1 < = x < = 1; by atomic percent, 30 < = a < = 90, and 10 < = b < = 50. According to the coating provided by the invention, the viscosity and thixotropy of the coating can be reduced through the interaction between characteristic functional groups of the PVB resin and between the characteristic functional groups and the alloy powder, wire drawing is not prone to occurring in the silk-screen printing process, products are not prone to being influenced by coating factors to show differences of all batches, and the weight increasing uniformity is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of permanent magnets, and in particular, relates to a coating and a preparation method thereof, a NdFeB substrate with a coating, and a NdFeB magnet. Background Art

[0002] Sintered NdFeB magnets are currently considered as functional materials necessary for energy saving and performance improvement, and their application scope and production volume are expanding year by year. In order to improve the magnetic properties of magnets and reduce the use of heavy rare earths, a grain boundary diffusion process can be used, such as preparing heavy rare earths (such as oxides, hydrides, fluorides and fluoride oxides of Tb or Dy) into a coating and applying it to the surface of sintered NdFeB magnets, and through diffusion treatment, the heavy rare earth elements diffuse from the surface of the sintered magnet along the inside of the magnet.

[0003] In order to further reduce the use of heavy rare earths, the inventors of this application tried to use light rare earth elements such as Pr and Nd to replace part of the heavy rare earth elements as coatings and applied them on the surface of the magnet substrate by screen printing. Further research found that although the performance of the magnet was improved, the surface properties of the coating changed after the light rare earth elements such as Pr and Nd replaced the heavy rare earth elements such as Dy and Tb. The prepared coating had problems such as poor fluidity, unstable thixotropy and high temperature sensitivity, resulting in poor uniformity of the coating thickness on the surface of the magnet substrate after screen printing, and fluctuations in the coating weight between batches and within batches, which in turn affected the magnetic properties of the magnet after diffusion treatment. The weight gain of the coating layer has a greater impact on the HcJ of the magnet after diffusion, and a slight change in the weight gain of the coating will cause a large fluctuation in the HcJ of the magnet. The content of the background technology section is only the technology known to the inventor and does not necessarily represent the prior art in this field. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a coating.

[0005] The coating provided by the present invention comprises PVB resin and alloy powder;

[0006] Wherein, the molecular chain ends of the PVB resin include amino groups and / or amide groups, and the side groups of the main molecular chain of the PVB resin include butyral groups, hydroxyl groups and acetoxy groups;

[0007] The alloy powder has a composition shown in formula (I):

[0008] (HRe (1-x) LqCy x ) a T 100-a-b M b , formula (I)

[0009] Wherein HRe includes Tb and / or Dy; LRe includes one or more of Nd, Pr, La, and Ce; T includes Fe and / or Co; M includes one or more of Al, Ga, Cu, Zn, Sn, Ni, and Si;

[0010] Wherein 0.1≤x≤1, preferably, 0.1≤x≤0.9;

[0011] Calculated in atomic percentage, 30≤a≤90, 10≤b≤50.

[0012] In some embodiments of the present invention, the contents of the butyral group, the hydroxyl group and the acetoxy group are 70% to 80%, 10% to 25% and 5% to 10% of the total amount of the side groups, respectively.

[0013] In some embodiments of the present invention, the weight average molecular weight of the PVB resin is 20,000-40,000.

[0014] In some embodiments of the present invention, the glass transition temperature of the PVB resin is 60°C to 75°C.

[0015] In some embodiments of the present invention, the viscosity value of the coating is set to A when the rotation speed is 5RPM and the temperature is 25°C, and the viscosity value of the coating is set to B when the rotation speed is 25RPM and the temperature is 25°C, (AB) / A≤20%.

[0016] In some embodiments of the present invention, the viscosity value of the coating is set to C at a speed of 3RPM and a temperature of 20°C, and the viscosity value of the coating is set to D at a speed of 3RPM and a temperature of 35°C, (CD) / C≤25%, preferably, (CD) / C≤10%.

[0017] In some embodiments of the present invention, D50 of the alloy powder is 2 μm to 8 μm.

[0018] In some embodiments of the present invention, the coating further comprises a solvent and a dispersant, and the mass ratio of the solvent, the dispersant, the PVB resin, and the alloy powder is 100:(0.2-2):(1-30):(150-500).

[0019] In some embodiments of the present invention, the solvent is an alcohol solvent or a mixture of an alcohol solvent and an ester solvent; and the dispersant is an amide organic compound.

[0020] The present invention also provides a method for preparing a coating, comprising:

[0021] Adding the dispersant into the solvent and mixing evenly to obtain a first mixed solution;

[0022] Adding PVB resin into the first mixed solution, dissolving it and mixing it evenly to obtain a second mixed solution; and

[0023] adding alloy powder to the second mixed liquid and mixing evenly to obtain the coating;

[0024] Wherein, the molecular chain ends of the PVB resin include amino groups and / or amide groups, and the side groups of the main molecular chain of the PVB resin include butyral groups, hydroxyl groups and acetoxy groups;

[0025] The alloy powder has a composition shown in formula (I):

[0026] (HRe (1-x) LqCy x ) a T 100-a-b M b , formula (I)

[0027] Wherein HRe includes Tb and / or Dy; LRe includes one or more of Nd, Pr, La, and Ce; T includes Fe and / or Co; M includes one or more of Al, Ga, Cu, Zn, Sn, Ni, and Si;

[0028] Wherein 0.1≤x≤1, preferably, 0.1≤x≤0.9;

[0029] Calculated in atomic percentage, 30≤a≤90, 10≤b≤50.

[0030] In some embodiments of the present invention, adding PVB resin into the first mixed solution, dissolving the mixture and then mixing the mixture evenly comprises:

[0031] The PVB resin is added into the first mixed liquid, and stirred fully in a water bath at 35° C. to 45° C., so that the PVB resin is dissolved and evenly mixed with the first mixed liquid.

[0032] In some embodiments of the present invention, adding alloy powder into the second mixed liquid and mixing uniformly comprises:

[0033] The alloy powder is added into the second mixed liquid, and the mixture is stirred for at least 2 hours in a water bath kept at 35° C. to 45° C., so that the alloy powder and the second mixed liquid are mixed evenly.

[0034] The present invention further provides a NdFeB substrate with a coating, characterized in that the surface of the NdFeB substrate includes a coating formed by coating and drying any of the above-mentioned coatings.

[0035] The present invention also provides a NdFeB magnet, which is obtained by subjecting the NdFeB substrate with coating to high-temperature diffusion treatment and tempering treatment.

[0036] The interaction between the characteristic functional groups of the PVB resin in the coating provided by the present invention and the interaction between the PVB resin and the alloy powder can reduce the viscosity and thixotropy of the coating while increasing the plasticity of the coating. Wiredrawing is not easy to occur during the coating process, the product is not easily affected by coating factors and shows differences between batches, and the weight gain uniformity is good.

[0037] The preparation method provided by the present invention can obtain a coating with good fluidity, low thixotropy, low shear viscosity mutation rate and low temperature sensitivity through a specific adding sequence.

[0038] The surface of the NdFeB substrate and NdFeB magnet with coating prepared by the present invention includes a coating formed by coating the coating. The coating has very good coating uniformity, and the magnetic properties of the prepared NdFeB magnet are excellent.

[0039] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] The accompanying drawings constituting a part of the present disclosure are used to provide a further understanding of the present disclosure. The illustrative embodiments of the present disclosure and their descriptions are used to explain the present disclosure and do not constitute improper limitations on the present disclosure.

[0041] FIG. 1( a ) and FIG. 1( b ) show the process of screen printing a coating onto the surface of a NdFeB magnet, wherein FIG. 1( a ) shows the stationary state of the scraper, and FIG. 1( b ) shows the moving state of the scraper.

[0042] Figure 2 A process flow chart for preparing a coating for NdFeB magnets provided by an embodiment of the present invention is shown.

[0043] Figure 3 A process flow chart for preparing NdFeB magnets provided by one embodiment of the present invention is shown.

[0044] Figure 4 The graphs showing the viscosity changes of Example 1-1 of the present invention and Comparative Example 1-2 at different rotation speeds measured at 25°C are shown.

[0045] Figure 5 The graphs showing the viscosity changes at different temperatures of Example 1-1 of the present invention and Comparative Example 1-2 are shown. DETAILED DESCRIPTION

[0046] In the following, only some exemplary embodiments are briefly described. As those skilled in the art will appreciate, the described embodiments may be modified in various ways without departing from the spirit or scope of the present invention. Therefore, the drawings and descriptions are considered to be exemplary and non-restrictive in nature.

[0047] The disclosure below provides many different embodiments or examples for implementing the present invention. In order to simplify the disclosure of the present invention, the components and settings of specific examples are described below. Of course, they are only examples, and the purpose is not to limit the present invention. In addition, the present invention can repeat reference numbers and / or reference letters in different examples, and this repetition is for the purpose of simplicity and clarity, which itself does not indicate the relationship between the various embodiments and / or settings discussed. In addition, the present invention provides various specific examples of processes and materials, but those of ordinary skill in the art can appreciate the application of other processes and / or the use of other materials.

[0048] In addition, unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as those generally understood by those of ordinary skill in the art to which the present invention belongs. It will also be understood that terms, such as those defined in commonly used dictionaries, should be interpreted as having a meaning consistent with their meaning in the context of the relevant technology and the present invention, and will not be interpreted in an idealized or overly formal sense unless explicitly defined in this article.

[0049] As used herein, "about" or "approximately" includes the stated value and means within an acceptable range of deviation from the particular value as determined by one skilled in the art, taking into account the measurement in question and the errors associated with the measurement of the particular quantity (i.e., the limitations of the measurement system). For example, "about" can mean within one or more standard deviations, or within ±30%, ±20%, ±10%, or ±5% of the stated value.

[0050] The following is a more detailed description of the specific embodiments of the present invention in conjunction with the accompanying drawings and examples, so that the scheme of the present invention and its advantages in various aspects can be better understood. However, the specific embodiments and examples described below are only for the purpose of illustration, rather than for limiting the present invention.

[0051] Figures 1(a) and 1(b) show the process of applying the coating to the surface of the NdFeB magnet by screen printing, wherein Figure 1(a) shows the static state of the scraper, and Figure 1(b) shows the moving state of the scraper. As shown in Figure 1(a), the coating is sprayed on the surface of the screen, and the ink knife scrapes it flat, so that the coating is roughly evenly spread on the surface of the screen. Then, as shown in Figure 1(b), the scraper is pressed down, and the screen is pressed by the scraper onto the surface of the magnet on the sample table, and the coating is applied to the surface of the magnet through the screen.

[0052] As mentioned above, the alloy powder made by replacing part of the heavy rare earth with light rare earth will have changes in the surface state and characteristics of the powder due to the change in composition. After being prepared into a coating, it will have problems such as poor fluidity, high thixotropy and high temperature sensitivity. The coating has poor fluidity and high thixotropy, and the range of viscosity changes with the shear rate of the scraper and the screen will become too wide, which will lead to a wide distribution of weight gain during screen printing, resulting in poor coating uniformity. The high temperature sensitivity of the coating will cause large fluctuations in coating uniformity between batches at ambient temperatures on different dates.

[0053] coating

[0054] In order to solve the above technical problems, the present invention provides a coating for NdFeB magnets. The coating comprises alloy powder and PVB resin. In some embodiments of the present invention, the coating further comprises a solvent and a dispersant. In some embodiments of the present invention, the mass ratio of the solvent, the dispersant, the PVB resin and the alloy powder may be 100: (0.2-2): (1-30): (150-500).

[0055] Among them, the dispersant within this range can ensure that the powder has a good dispersion effect in the solvent, and the PVB resin in this ratio can form a good coating effect on the powder and reduce the risk of agglomeration, thereby limiting the ratio of the solvent, dispersant and resin.

[0056] Among them, the solid-liquid ratio within this specified range can ensure that the coating has good fluidity and low thixotropy. If the solid powder ratio is lower than this range, the coating is too thin, bubbles are easily generated on the large surface of the coating after printing and coating, and the sides are easy to flow, resulting in poor coating quality. If the solid powder ratio is higher than this range, the coating fluidity is too poor and it is difficult to achieve uniform coating.

[0057] The alloy powder used in the present invention has a composition shown in formula (I):

[0058] (HRe (1-x) LqCy x ) a T 100-a-b M b , formula (I)

[0059] Wherein, HRe includes Tb and / or Dy. In some embodiments of the present invention, HRe may be only Tb, or HRe may be only Dy. In some embodiments of the present invention, in addition to Tb and / or Dy, HRe may also include other heavy rare earth elements, for example, HRe may be Tb and Ho, or HRe may be Dy and Ho.

[0060] Wherein, LRe includes one or more of Nd, Pr, La, and Ce, and LRe may also include other light rare earth elements, for example, LRe may be Nd and Sm, or LRe may be Pr and Sm. T includes Fe and / or Co. M includes one or more of Al, Ga, Cu, Zn, Sn, Ni, and Si.

[0061] Among them, calculated in atomic percentage, 30≤a≤90, 10≤b≤50.

[0062] In the present invention, 30≤a≤90, preferably 40≤a≤80. When a<40, the rare earth content in the alloy is too low, and the non-rare earth elements T and M content are too high, which are easy to react with the main phase in the diffusion substrate and consume the main phase grains, thereby affecting the residual magnetism after diffusion; when a>80, the rare earth elements in the alloy powder are too high, and the rare earth-rich phase is mainly formed in the grain boundary phase, which is not conducive to the efficient use of rare earths.

[0063] In the present invention, 10≤b≤50. When b<10, the proportion of low melting point elements in the alloy is too low, and a large amount of rare earth-rich phases will be generated in the grain boundary phase, affecting the utilization rate of rare earth; when b>50, the low melting point elements generate a large amount of grain boundary phases between the grains, which significantly reduces the proportion of the main phase of the magnet, resulting in a significant reduction in magnetic properties.

[0064] In the present invention, 0.1≤x≤1, preferably 0.1≤x≤0.9. When x>0.9, the proportion of HRe provided in the alloy is too low, and the new shell formed has insufficient effect on improving the overall HcJ; when x<0.1, HRe is easily enriched in the grain boundary phase, reducing the cost-effectiveness of diffusion.

[0065] In the present invention, the light rare earth LRe can replace about 10% to 100% of the heavy rare earth HRe (i.e., 0.1≤x≤1). In some embodiments of the present invention, the light rare earth can replace about 20% to about 80% of the heavy rare earth. In other embodiments of the present invention, the light rare earth can replace about 30% to about 70% of the heavy rare earth. In other embodiments of the present invention, the light rare earth can replace about 40% to about 60% of the heavy rare earth. In other embodiments of the present invention, the light rare earth can replace about 50% of the heavy rare earth.

[0066] In some embodiments of the present invention, the particle size (D50) of the alloy powder is about 2 μm to about 8 μm. Preferably, the D50 of the alloy powder is about 2.5 μm to about 5 μm. The fluidity of the coating prepared at this particle size is better.

[0067] The PVB (polyvinyl butyral) resin used in the present invention is a long-chain high molecular polymer, and its molecular structure is a product obtained by acetalization reaction of polyvinyl alcohol and aldehyde organic compound monomers, and polyvinyl alcohol is obtained by hydrolysis or alcoholysis of polyvinyl acetate (or vinyl acetate). The molecular long-chain structure provides a lower glass transition temperature, so that the PVB resin has good tensile strength and impact strength.

[0068] Wherein, the molecular chain end of the PVB resin includes an amino group and / or an amide group, preferably an amide group, wherein the amino group and / or the amide group may be at both ends of the molecular chain or at one end thereof. The amino group and the amide group may enable the alloy powder to have better dispersibility and stability in the coating. In the present invention, by selecting an amino group and / or an amide group at the molecular chain end, the alloy powder particles having a light rare earth component may interact with these characteristic functional groups through active sites or by forming coordination bonds, thereby enabling the alloy powder to have better dispersibility and stability in the coating.

[0069] Furthermore, the side groups of the main molecular chain of the PVB resin include butyral, hydroxyl (e.g., vinyl alcohol) and acetoxy (e.g., vinyl acetate). The six-membered ring-shaped butyral structure can improve the strength of the molecular chain, and the solubility, compatibility and water resistance are greatly increased with the increase of the butyral content. The hydroxyl structure provides tear strength and good adhesion, and the water solubility increases with the increase of the hydroxyl value. The water resistance of the product increases with the increase of the acetoxy content.

[0070] In some embodiments of the present invention, the content of butyral groups may be about 70% to about 80% of the total amount of side groups, preferably about 75%; the content of hydroxyl groups may be about 5% to about 15% of the total amount of side groups, and the content of acetoxy groups may be about 15% to about 25% of the total amount of side groups. The group content described herein refers to the quantitative content of the groups. At this content, the interaction and coordination of the various groups can obtain a coating with good performance. Since polymers exist in the form of molecular coils in solvents, molecules are entangled with each other, and polar molecules interact with each other due to polar forces. When the molecular chains are sheared, conformational changes, disentanglements, and molecular chain stretching are prone to occur, and the molecular plasticity increases. After the shear force is removed, due to the inherent entropy, the elastic polymers will return to the molecular coil state, so most polymer solutions have shear thinning characteristics. The present invention sets the molecular chain side groups to include butyral, hydroxyl and acetoxy groups, and controls the proportion of each of them, especially the low proportion of hydroxyl groups. When the coating contains light rare earth metal ions, the bonding effect between macromolecules with low shear sensitivity (such as coordination effect) can be reduced, thereby adjusting the thixotropy of the polymer solution.

[0071] In some embodiments of the present invention, the weight average molecular weight of the PVB resin used is in the range of about 20,000 to about 40,000. The PVB resin at this molecular weight can make the alloy powder have better dispersibility and stability in the coating. Optionally, the glass transition temperature of the PVB resin is about 60° C. to about 75° C.

[0072] In some embodiments of the present invention, the PVB resin may be one or more of the polyvinyl butyral resins having grades of B-98, B-90, B-79, B-76, a weight average molecular weight range of about 20,000 to about 40,000, and a glass transition temperature of about 60°C to about 75°C.

[0073] In some embodiments of the present invention, the solvent used is an organic solvent, which may be an alcohol solvent or a mixture of an alcohol solvent and an ester solvent based on the solubility characteristics of the PVB resin, including but not limited to one or more of terpineol, ethanol, methanol, polyethylene glycol, n-propanol, isopropanol, n-butanol, ethyl acetate, n-butyl acetate, etc.

[0074] In some embodiments of the present invention, the dispersant used is an amide organic substance, that is, an organic substance in which the hydroxyl group of the carboxylic acid in the molecular structure is replaced by an amino group or an amine group, including but not limited to oleamide, stearic acid amide, erucic acid amide, oleoyl glycol amine, etc.

[0075] The coating provided by the invention has low viscosity, good fluidity, low thixotropy, low shear viscosity mutation rate, low temperature sensitivity, good uniformity of magnet weight gain within each batch and between batches, and significantly improved coercive force.

[0076] Method for preparing coating.

[0077] Figure 2 A method for preparing a coating for NdFeB magnets provided by an embodiment of the present invention is shown, comprising the following steps S21 to S23.

[0078] S21: adding the dispersant into the solvent and mixing them evenly to obtain a first mixed solution.

[0079] The selection of dispersant and solvent is as described above and will not be repeated here. In some embodiments of the present invention, the amount of dispersant is about 0.2wt% to about 2wt% of the amount of solvent. In the present invention, wt% is the mass percentage. Optionally, this step is carried out under a water bath insulation condition at a temperature of about 35°C to about 45°C.

[0080] S22: adding PVB resin into the first mixed solution, dissolving the mixture, and mixing the mixture evenly to obtain a second mixed solution.

[0081] As mentioned above, the molecular chain ends of the PVB resin include amino and / or amide groups, and the side groups of the main chain include butyral groups, hydroxyl groups and acetoxy groups, which are not described in detail. In some embodiments of the present invention, the amount of PVB resin used is about 1wt% to about 30wt% of the amount of solvent used.

[0082] Optionally, step S22 is specifically as follows:

[0083] PVB resin is added to the first mixed liquid, and the mixture is stirred fully in a water bath at a temperature of about 35° C. to about 45° C. to dissolve the PVB resin and mix it evenly with the first mixed liquid, thereby obtaining a second mixed liquid.

[0084] S23: adding the alloy powder into the second mixed liquid and mixing them evenly to obtain a coating.

[0085] The specific composition of the alloy powder is as described above and will not be described again. In some embodiments of the present invention, the amount of the alloy powder is about 150 wt % to about 500 wt % of the amount of the solvent.

[0086] Optionally, step S23 is specifically as follows:

[0087] The alloy powder is added to the second mixed liquid, and the mixture is stirred for at least 2 hours in a water bath kept at about 35° C. to about 45° C., so that the alloy powder and the second mixed liquid are evenly mixed, thereby obtaining a coating.

[0088] In the present invention, the water bath temperature in the above steps is much lower than the glass transition temperature of PVB, which can ensure that the PVB resin is fully dissolved in the solvent, and the resin molecules and the alloy powder form good mutual bonds and interactions, so that the coating system is evenly dispersed and not easy to settle, and avoid the spontaneous cross-linking and curing reaction of the PVB resin molecular segments that is easily accelerated in the high temperature water bath, causing the resin to denature.

[0089] The preparation method provided by the present invention can obtain a coating with good fluidity, low shear viscosity mutation rate and low temperature sensitivity through a specific adding sequence.

[0090] Neodymium iron boron magnet and preparation method thereof

[0091] Figure 3 A method for preparing a neodymium iron boron magnet according to an embodiment of the present invention is shown, comprising the following steps S31 to S33.

[0092] S31: Pre-treating the magnet substrate.

[0093] The pretreatment is generally pickling, which takes about 10s to about 30s. After pickling, weighing is performed.

[0094] S32: Apply paint.

[0095] Optionally, this step is specifically as follows:

[0096] The coating obtained in steps S21 to S23 is applied to the surface of the magnet substrate after pickling by screen printing. After coating, it is dried at a temperature of about 100° C. to about 120° C. and kept warm for about 20 minutes to about 30 minutes.

[0097] Both sides of the magnet need to be screen printed and coated. After the first side is coated and dried, the second side is coated and dried. After both sides are coated and dried, the coating weight gain test is performed.

[0098] S33: Diffusion treatment and tempering treatment.

[0099] Optionally, this step is specifically as follows:

[0100] Degreasing is performed at a temperature of about 400°C for about 1 hour;

[0101] After the heat preservation is completed, the primary diffusion is carried out at a temperature of about 950°C for about 4h to about 6h;

[0102] After the primary diffusion is completed, secondary annealing is carried out at a temperature of about 550°C and kept for about 1 hour.

[0103] After heat treatment, the magnetic properties were measured.

[0104] The surface of the NdFeB substrate with coating prepared by the present invention includes a coating formed by coating and drying the aforementioned coating. The coating method can be screen printing, spraying, dipping, etc. The coating uniformity is very good, and the NdFeB magnet prepared after diffusion treatment and tempering treatment has excellent magnetic properties.

[0105] The present invention is described below with reference to specific embodiments. The process condition values ​​taken in the following embodiments are all exemplary, and the possible value ranges are as shown in the above invention content. For process parameters not specifically noted, conventional techniques can be used. Unless otherwise specified, the reagents and instruments used in the technical solutions provided by the present invention can be purchased from conventional channels or the market.

[0106] The coating performance characterization methods used in the following examples and comparative examples are as follows, and the remaining detection methods are conventional detection methods in the industry:

[0107] The change of coating viscosity at different rotation speeds is measured by a rotational viscometer to characterize the viscosity change caused by shear force changes during the coating process, such as screen printing coating. When the rotation speed is ≤3RPM, it is similar to the static state. When the rotation speed is >3RPM, the force of the coating when the scraper moves is simulated. Due to the start and stop, reciprocating, lifting process of the scraper and the relative position and shear rate of the coating on the screen will change. Therefore, different rotation speeds are set to test the state change of the coating during the entire screen printing coating process. In the following embodiments and comparative examples, the formula (AB) / A is selected to characterize the shear viscosity mutation rate of the coating, that is, the rate of change of the viscosity value when the coating is subjected to different shear forces at different rotation speeds, where A is the viscosity value of the coating measured at 25°C and 5RPM, and B is the viscosity value of the coating measured at 25°C and 20RPM. In the following embodiments and comparative examples, (CD) / C is selected to characterize the temperature sensitivity of the coating at normal ambient temperature, where C is the viscosity value of the coating measured at 20°C and 3RPM, and D is the viscosity value of the coating measured at 35°C and 3RPM.

[0108] Example 1-1

[0109] This embodiment prepares a coating, and the specific steps are as follows:

[0110] Weigh about 2g of pinene alcohol, add about 0.02g of oleic acid amide, keep warm in a water bath at about 40℃, stir for about 10min to mix evenly, and obtain the first mixed solution. Weigh about 0.02g of PVB resin, add it to the first mixed solution, keep warm in a water bath at about 40℃, stir for about 1h to mix evenly, and obtain the second mixed solution. Weigh about 8g of alloy powder and add it to the second mixed solution, mix evenly, keep warm in a water bath at about 35℃ and stir for about 2.5h.

[0111] Among them, the alloy powder composition is (Tb 0.5 Pr 0.5 ) 70 Co 10 Cu 20 (atomic percentage), the powder particle size D50 is about 2.5μm, the PVB resin is Butvar B-79, the weight average molecular weight is 25000-40000, the contents of butyral group, hydroxyl group and acetoxy group are 75%, 10% and 15% respectively, and its glass transition temperature is 62℃~67℃.

[0112] The viscosity of the coating at different speeds at 25°C and at different temperatures at 5 RPM was measured using a rotational viscometer. Figure 4 , Figure 5 The shear viscosity mutation rate and temperature sensitivity are calculated and shown in Table 1.

[0113] Examples 1-2 to 1-4

[0114] The only difference between Examples 1-2 to 1-4 and Example 1-1 is that the compositions of the alloy powders of Examples 1-2 to 1-4 are (Tb 0.75 Pr 0.25 ) 80 Cu 20 ,(Tb 0.5 Pr 0.5 ) 65 Co 15 Cu 20 , Pr 70 Co 10 Cu 20 .

[0115] The shear viscosity mutation rate and temperature sensitivity of the coating are shown in Table 1.

[0116] Examples 1-5

[0117] The only difference between this embodiment and embodiment 1-1 is that the PVB resin used is Butvar B-98, with a weight average molecular weight of 20,000 to 35,000, the contents of butyral group, hydroxyl group and acetoxy group are 75%, 20% and 5% respectively, and its glass transition temperature is 66°C to 70°C.

[0118] The shear viscosity mutation rate and temperature sensitivity of the coating are shown in Table 1.

[0119] Examples 1-6

[0120] The only difference between this embodiment and embodiment 1-1 is that the D50 of the alloy powder used is 1 μm.

[0121] The shear viscosity mutation rate and temperature sensitivity of the coating are shown in Table 1.

[0122] Examples 1-7

[0123] The only difference between this embodiment and embodiment 1-1 is that the amount of PVB resin used is 0.7 g.

[0124] The shear viscosity mutation rate and temperature sensitivity of the coating are shown in Table 1.

[0125] Examples 1-8 to 1-10

[0126] The only difference between Examples 1-8 to 1-10 and Example 1-1 is that the compositions of the alloy powders of Examples 1-8 to 1-10 are (Dy 0.7 Nd 0.3 ) 60 Co5Cu 15 Al 20 、(Dy 0.8 Pr 0.2 ) 40 Co20 Cu 40 、(Dy 0.4 Pr 0.6 ) 60 Co 25 Ga 15 .

[0127] The shear viscosity mutation rate and temperature sensitivity of the coating are shown in Table 1.

[0128] Comparative Example 1-1

[0129] The difference between this comparative example and Example 1-1 is that the composition of the alloy powder is Tb 90 Co5Cu5.

[0130] The shear viscosity mutation rate and temperature sensitivity of the coating are shown in Table 1.

[0131] Comparative Example 1-2

[0132] The only difference between this comparative example and Example 1-1 is that the PVB resin is Butvar B-98, the weight average molecular weight is 70000-90000, and the glass transition temperature is 68-74°C.

[0133] Use a rotational viscometer to measure the viscosity of the coating at different speeds at 25°C and at different temperatures at 3RPM. Figure 4 , Figure 5 , calculate the shear viscosity mutation rate and temperature sensitivity, see Table 1.

[0134] Comparative Examples 1-3 to 1-5

[0135] The only difference between Comparative Examples 1-3 to 1-5 and Example 1-1 is that their PVB resins are respectively PVB resins without amino groups and amide groups at the ends of the resin molecules, PVB resins in which hydroxyl groups account for about 30% of the side groups of the resin molecules, and PVB resins in which acetoxy groups account for about 1% of the side groups of the resin molecules.

[0136] The shear viscosity mutation rate and temperature sensitivity of the coating are shown in Table 1.

[0137] Table 1

[0138]

[0139]

[0140]

[0141] As can be seen from Table 1, the coating provided by the present invention has low viscosity, good fluidity, low shear viscosity mutation rate, and low temperature sensitivity.

[0142] from Figure 4 and Figure 5 It can be seen that compared with Example 1-2, the anti-mutation ability of the coating of Example 1-1 is significantly improved. When the coating is at a low speed (3RPM, similar to a static state), the viscosity reaches the maximum peak value; when the speed is increased from 3RPM to 30RPM, the fluctuation range of the coating viscosity change is within 20%. In the range of the speed of 12 to 30RPM, the kinematic viscosity value of the coating remains relatively stable, which can ensure that when the screen printing coating is applied, when the scraper is in different printing positions, the coating has a good anti-mutation ability. In addition, when the temperature rises from 15°C to 40°C, the viscosity value fluctuation is reduced from more than 45% to less than 25%, and when the temperature rises from 20°C to 35°C, the viscosity change is reduced to less than 10%, indicating that when the ambient temperature suddenly changes, the coating can still maintain a relatively stable state, which is conducive to maintaining the coating consistency of samples at different times and between different batches.

[0143] Example 2-1

[0144] In this embodiment, a neodymium iron boron magnet is prepared, and the specific steps are as follows:

[0145] The magnet blanks were cut to obtain magnet substrates with a size of 9×9×4 mm (4 mm direction is the orientation direction), a total of 25 pieces. After about 15 seconds of pickling pretreatment, each piece was weighed separately, and the weight was recorded as W1.

[0146] After pickling, the magnet substrate is screen-printed and coated on one surface of the substrate of 9×4 mm, and then dried at about 100°C for about 30 minutes, and then the coating and drying are repeated on the other surface of 9×4 mm to obtain a NdFeB substrate with a coating. The NdFeB substrates with coatings are weighed separately, and the weight is recorded as W2. The weight gain rate of each substrate coating and its range value are calculated, as shown in Table 2.

[0147] Then, the coated NdFeB substrate was degreased at about 400°C for about 1 hour; primary diffusion was performed at about 950°C for about 4 hours; secondary tempering was performed at about 550°C for about 1 hour to obtain NdFeB magnets. The magnetic properties of each piece were measured, and the Br fluctuation (Br extreme value), coercive force fluctuation (HcJ extreme value) and coercive force increment (△HcJ = NdFeB magnet HcJ-blank HcJ) between each magnet were calculated, see Table 2.

[0148] The coating used is the coating prepared in Example 1-1, and the magnet blank is a commercial sintered NdFeB product with a grade of N42M.

[0149] Examples 2-2 to 2-10

[0150] The only difference between Examples 2-2 to 2-10 and Example 2-1 is that the coating used is the coating prepared in Examples 1-2 to 1-10.

[0151] The coating weight gain rate and magnet properties are shown in Table 2.

[0152] Comparative Examples 2-1 to 2-5

[0153] The difference between Comparative Examples 2-1 to 2-5 and Example 2-1 is that the coating used is the coating prepared in Comparative Examples 1-1 to 1-5.

[0154] The coating weight gain rate and magnet properties are shown in Table 2.

[0155] Table 2

[0156]

[0157]

[0158] As can be seen from Table 2, the coating provided by the present invention has a low extreme value of coating weight gain rate, and the coating is very uniform. The obtained NdFeB magnet has excellent magnetic properties and small fluctuations in magnetic properties.

[0159] Obviously, the above embodiments are merely examples for clearly explaining the present invention, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the protection scope of the present invention.

Claims

1. A coating, characterized in that: Including PVB resin and alloy powder; Wherein, the molecular chain ends of the PVB resin include amino groups and / or amide groups, and the side groups of the main molecular chain of the PVB resin include butyral groups, hydroxyl groups and acetoxy groups; The alloy powder has a composition shown in formula (I): (HRe (1-x) LRe x ) a T 100-a-b M b , formula (Ⅰ) Wherein HRe includes Tb and / or Dy; LRe includes one or more of Nd, Pr, La, and Ce; T includes Fe and / or Co; M includes one or more of Al, Ga, Cu, Zn, Sn, Ni, and Si; Wherein 0.1≤x≤1, preferably, 0.1≤x≤0.9; Calculated in atomic percentage, 30≤a≤90, 10≤b≤50.

2. The coating according to claim 1, characterized in that The contents of the butyral group, the hydroxyl group and the acetoxy group are respectively 70% to 80%, 10% to 25% and 5% to 10% of the total amount of the side groups.

3. The coating according to claim 1, characterized in that The weight average molecular weight of the PVB resin is 20,000-40,000.

4. The coating according to claim 1, characterized in that The glass transition temperature of the PVB resin is 60°C to 75°C.

5. The coating according to claim 1, characterized in that The viscosity value of the coating at a rotation speed of 5 RPM and a temperature of 25° C. is set to A, and the viscosity value of the coating at a rotation speed of 25 RPM and a temperature of 25° C. is set to B, (AB) / A≤20%.

6. The coating according to claim 1, characterized in that The viscosity value of the coating is set to C at a rotation speed of 3RPM and a temperature of 20°C, and the viscosity value of the coating is set to D at a rotation speed of 3RPM and a temperature of 35°C, (CD) / C≤25%, preferably, (CD) / C≤10%.

7. The coating according to claim 1, characterized in that The D50 of the alloy powder is 2 μm to 8 μm.

8. The coating according to claim 1, characterized in that It also includes a solvent and a dispersant, and the mass ratio of the solvent, the dispersant, the PVB resin, and the alloy powder is 100: (0.2-2): (1-30): (150-500).

9. The coating according to claim 8, characterized in that The solvent is an alcohol solvent or a mixture of an alcohol solvent and an ester solvent; The dispersant is an amide organic compound.

10. A method for preparing a coating, characterized in that: include: Adding the dispersant into the solvent and mixing evenly to obtain a first mixed solution; Adding PVB resin into the first mixed solution, dissolving it and mixing it evenly to obtain a second mixed solution; as well as adding the alloy powder into the second mixed liquid and mixing evenly to obtain the coating; Wherein, the molecular chain ends of the PVB resin include amino groups and / or amide groups, and the side groups of the main molecular chain of the PVB resin include butyral groups, hydroxyl groups and acetoxy groups; The alloy powder has a composition shown in formula (I): (HRe (1-x) LRe x ) a T 100-a-b M b , formula (I) Wherein HRe includes Tb and / or Dy; LRe includes one or more of Nd, Pr, La, and Ce; T includes Fe and / or Co; M includes one or more of Al, Ga, Cu, Zn, Sn, Ni, and Si; Wherein 0.1≤x≤1, preferably, 0.1≤x≤0.9; Calculated in atomic percentage, 30≤a≤90, 10≤b≤50.

11. The preparation method according to claim 10, characterized in that: Adding PVB resin into the first mixed solution, dissolving it and mixing it evenly comprises: Add the PVB resin to the first mixed solution, and stir thoroughly in a water bath at 35° C. to 45° C. to dissolve the PVB resin and mix it evenly with the first mixed solution; Adding the alloy powder into the second mixed liquid and mixing evenly comprises: The alloy powder is added into the second mixed liquid, and the mixture is stirred for at least 2 hours in a water bath kept at 35° C. to 45° C., so that the alloy powder and the second mixed liquid are evenly mixed.

12. A NdFeB substrate with a coating, characterized in that: The surface of the NdFeB substrate includes a coating formed by coating and drying the coating material as claimed in any one of claims 1 to 9.

13. A neodymium iron boron magnet, characterized in that: The NdFeB substrate with coating as claimed in claim 12 is obtained by diffusion treatment and tempering treatment.